(untitled) (RuMoRes, 2023)
This article aims to debate the function and role of media criticism in the organization of content present on platforms or audiovisual aggregators. From the understanding that aspects of criticism influence from the production processes and its elaboration, which are articulated to the demands of filmmakers and are consolidated in the reception and mediation with the public, building a network from a critical complex found in media mediation. This production shows a media circuit of platforms or aggregators on three levels: a) the criticism of the producers; b) the critical mediation of curatorship; and c) the critical reception of the public.